Socioeconomic and geographical inequalities in delivery by cesarean section among women in Bangladesh, 2004-2017 - Satyajit Kundu; Azaz Bin Sharif; Syed Sharaf Ahmed Chowdhury; Sadia Afroz; Rakhi Dey; Ahmed Hossain (BMC, 2024)
Abstract Background There is a dearth of evidence on the trends and inequalities in utilizing cesarean section (CS) among women in Bangladesh. Hence, this study aimed to estimate the socioeconomic and geographical inequalities in delivery by CS among Bangladeshi women from 2004 to 2017. Methods Data from Bangladesh Demographic and Health Survey 2004, 2007, 2011, 2014, and 2017 were analyzed using the WHO's Health Equity Assessment Toolkit (HEAT) software. Inequalities were measured using four summary measures: Difference (D), Population Attributable Risk (PAR), Population Attributable Fraction (PAF), and Ratio (R). Socioeconomic inequalities were assessed using two equity dimensions: household wealth status, and level of education, while geographical disparities were measured using two equity dimensions: place of residence, and sub-national regions. For each measure, point estimates and their 95% confidence intervals were reported. Results An increasing trend in the prevalence (weighted) of CS in Bangladesh use was found from 4.50% in 2004 to 32.73% in 2017 We found significant socioeconomic inequalities in CS in every survey point, with a higher concentration of CS among the rich (in 2017, PAR = 28.57; 95% CI: 26.69-30.46) indicating a pro-rich inequality, and higher educated (in 2017, PAF = 23.97; 95% CI: 12.26-35.68) sub-groups. We also identified significant geographical disparities in CS with a higher concentration of CS among people from urban areas (in 2017, PAR = 10.99; 95% CI: 10.19-11.79), and a coastal region (Khulna division) (in 2017, PAF: 30.48 (95% CI: 18.66-42.30). Conclusion We observed both socioeconomic and geographical inequalities in CS exist in Bangladesh, though the trends of these inequalities were curved over time. Thus, it is important to comprehend these pro-rich and geographical inequalities better and implement appropriate interventions and policies to alleviate them.